Reprofiling Of Ormeloxifene For Its Neuroprotective Activity Against Monosodium Glutamate And Aluminium Chloride Induced Neurotoxicity In Rats - G, Suma; Shalavadi, Mallappa; Teli, Shubham; U, Mounashree; N, Rajashekhar; Hiremath, Shivaraj; H, Basavaraj (Journal of Neonatal Surgery, 2025)
Background: Monosodium glutamate (MSG) and Aluminium chloride (AlCl3) are known to induce neurotoxicity, which can lead to cognitive deficits and neuronal damage. Due to the neuroprotective role of Ormeloxifene, it is evaluated against chemically (MSG) and (AlCl3) induced neurotoxicity in rats. Materials & Methods: Male Wistar albino rats were divided into two neurotoxicity models with 60 rats in each model. Rats were administered ormeloxifene at different doses (2.5, 5.1 and 10.2 mg/kg p.o) for 14 days AlCl3 model and 21 days MSG model. Neurobehavioral parameters such as locomotor activity, muscle coordination and spatial memory were carried out. Antioxidant enzyme estimated such as lipid peroxidation (LPO) and glutathione (GSH) along with acetylcholinesterase (AChE). Histopathology studies were also carried out. Results: Ormeloxifene co-treatment significantly reduced cognitive deficits, improved locomotor activity, muscle coordination, reference memory and spatial memory. It also reduced acetylcholinesterase (AchE) and lipid peroxidation (LPO) activity, while increasing glutathione (GSH) concentration. Histopathology reports showed reduced neuronal damage. Conclusion: Ormeloxifene demonstrated neuroprotective effects against MSG and AlCl3-induced neurotoxicity in rats, potentially due to its ability to activate kinases and inhibit nuclear factor (NF)-kB induced transcription. These findings suggest Ormeloxifene as a potential therapeutic agent for neuroprotection